Efektivitas Terapi Dzikir dalam Menurunkan Risiko Perilaku Kekerasan pada Pasien Skizofrenia di Panti Gramesia Cirebon - Ruswati Ruswati; Berlian Ayu Rahmawati; Duri Harto (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Schizophrenia is a chronic mental disorder characterized by disturbances in the mind, emotions, and behavior that can affect an individual's ability to carry out daily activities. According to the World Health Organization (WHO, 2022), there are approximately 24 million people with schizophrenia worldwide, while in Indonesia the prevalence reaches 1.8 per 1,000 population. This condition is often accompanied by the risk of violent behavior that can harm oneself and others. Based on data from the Panti Gramesia Cirebon, 24 patients were recorded at risk of violent behavior due to schizophrenia. One intervention that can be provided to reduce this risk is spiritual therapy, specifically through the practice of dhikr, which is believed to provide mental peace and reduce agitation levels in patients. This paper uses a case study design with a nursing process approach that includes the stages of assessment, establishing a nursing diagnosis, intervention planning, implementation, and evaluation. The case subject is Ms. S, a patient at risk of violent behavior due to schizophrenia. The intervention provided was spiritual therapy dhikr for three consecutive days with the assistance of a psychiatric nurse. The implementation results showed a decrease in symptoms in the form of reduced verbal threats, decreased agitation, increased patient cooperation, and active participation in spiritual activities. Further evaluation showed the achievement of short-term and long-term goals, namely a reduced risk of violent behavior and increased emotional calm of the patient. The findings of this case study indicate that spiritual therapy dhikr is an effective intervention that can be applied in psychiatric nursing care, especially for schizophrenia patients at risk of violent behavior. Therefore, it is recommended that dhikr therapy be made a routine and integrated intervention in healthcare facilities to support patient recovery holistically.